Performance studies the basics - Micu, Andreea S. (The basics, 2022)
"Performance Studies: The Basics offers an overview of the multiple, often overlapping definitions of performance, from performance art, performance as everyday life, and ritual to the performative dimensions of identity, such as gender, race, and sexuality. This book defines the interdisciplinary field of Performance Studies as it has evolved in the past four decades at the intersection of academic scholarship and artistic and activist practices. It discusses performance as an important embodied form of knowledge production and transmission, highlighting its intersections with critical theory, and arguing for the importance of performance in the study of human behaviour and social practices. Complete with helpful a glossary, bibliography, and suggestions for future reading, this book is an ideal starting point for those studying Performance Studies as well as general readers with an interest in the subject."--Provided by publisher.